Come va corretto il corrottissimo v. 202 di Aegritudo Perdicae? - Zurli, Loriano (AL. Rivista di studi di Anthologia Latina, 2024)
Abstract Using the support of paleography in examining the mechanisms of chain errors present in the second part of the verse, and above all through a reasonable exegesis of the text, the correction of the corrupt v. 202 of Aegritudo Perdicae is provided.